Energy policies and regulations in the built environment; a policy perspective - Benonia Tinarwo; Farzad Pour Rahimian; Mina Najafi (Urbanization, Sustainability and Society)
Purpose – This study aims to explore and analyse building energy performance (BEP) policies and regulations worldwide. It presents a perspective on the status quo of policy packages for the built environment. This study spans the six years between 2018 and 2023 to give a broad overview of the BEP policy landscape. Design/methodology/approach – An exploratory search of secondary sources was conducted within a six-year timeline. The six-year period enabled the creation of a pre- and post-COVID baseline through which comparisons of policy trends could be made. The International Energy Agency (IEA) and Scopus databases were the principal sources of relevant literature. A data extraction tool and four research questions were used to ensure the relevance of the selected sources. The primary limitation of this work is that the chosen time frame limited the number of policies and regulations investigated. Findings – At the time of writing this paper, 272 were retrieved from the IEA database, together with 65 eligible studies from the Scopus database. After data analysis, it was established that most national policies target renewable energy installations, heating and cooling of buildings, net-zero ambitions, fiscal instruments and long-term national interests. However, most studies focus on BEP policy assessment, renewable energy and the social impact of policies. Furthermore, four main findings emerged from the analysed data. These point to fragmentation of policy goals across the BEP landscape, institutional influence in energy policy formulation and little consideration of socio-economic-environmental impacts within BEP policy packages. Originality/value – This research contributes to the discourse on BEP policies and regulations by bringing BEP policy to the forefront. It highlights a fragmented BEP policy landscape and advocates for improved collaboration between academia, the private sector and policymakers to encourage accountability for the life-cycle energy performance of buildings and their services within policy frameworks. Additionally, this research identifies a need for integrative and holistic policy solutions.